Distal Radial Artery Access in comparison to Forearm Radial Artery Access for Cardiac Catheterization: A Randomized Controlled Trial (DARFORA Trial) - Yunis Daralammouri; Zaher Nazzal; Yahya S. Mosleh; Heba K. Abdulhaq; Zafer Y. Khayyat; Yousef El Hamshary; Murad Azamtta; Ahmed Ghanim; Fateh Awwad; Sajed Majadla; Mosab Maree; Jihad Hamaida; et al. (Journal of Interventional Cardiology)
Background. In our clinical practice, conventional radial access has been employed routinely for coronary procedures. The distal radial artery (DRA) access site has recently emerged as a novel technique in cardiac procedures. Objectives. This study compares distal radial access to standard forearm radial access (FRA) in terms of feasibility, outcomes, and complications. Method. This prospective, randomized trial was conducted at a single center. The patients were chosen from An-Najah National University Hospital’s catheterization laboratory between December 2019 and November 2020. A total of 209 patients were randomized into two groups: DRA group (n = 104) and FRA group (n = 105). Results. Access was successful in 98% of patients in both the groups. The DRA group had a longer puncture duration and a higher number of attempts (duration: 56.6 ± 61.1 s DRA vs. 20.0 ± 18.4 s FRA, p<0.001, attempts: 1.9 ± 1.3 DRA vs. 1.2 ± 0.60 FRA, p<0.001). Puncture-associated pain was greater in the DRA group (4 ± 2.2 DRA vs. 3 ± 2.1 FRA, p=0.001). There were two radial artery occlusions in the FRA group and none in the DRA group (p=0.139). Percutaneous coronary intervention (PCI) was performed in 26% of the DRA group and 37.1% of the FRA group. The DRA group had significantly shorter procedure times (p=0.006), fluoroscopy times (p=0.002), and hemostasis times (p=0.002). Over time, the learning curve demonstrated improved puncture duration and a decrease in the number of puncture attempts. Conclusions. DRA is a safe and practical alternative to FRA for coronary angiography and intervention. The overtime learning curve is expected to improve puncture-related outcomes.